Electrochemical Etching Gold Tips - M.Salih, Araz; A. S. Sadiq Mayi , Diyar (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
In this work, we propose a simple and easy method to produce sharp and smooth conical gold tips for atomic force microscope and scanning near-field optical microscopy. The method is electrochemically etching process, based on gold, Pt wire and HCl acid (37%) as a solution. Comparing to other methods, we use only HCl as electrolyte. A function generator was used to produce rectangular pulse wave with 3 kHz and 7 V to obtain smooth and very sharp conical tip with diameter less than 10 nm. By controlling etching parameters (pulse shape, frequency and voltage), the fabricated etching tip achieved about 80% yields. Moreover, the etching time is about 13 second, which is very fast etching process. This method provides a suited tip for tip-enhanced Raman scattering, adiabatic nanofocusing of aperturless-scanning near-field optical microscopy and field emission electron microscopy.